Performance Analysis of Ki Ageng Gribig Road Section from Malang - Pandaan Toll Gate Development Effect - Rizqi, Utin Winny; Oktaviastuti, Blima (Jurnal Fondasi, 2023)
Transportation is one of the driving forces for growing a region. Increase in population and the economic growth of a region resulted in the community needed facilities are increasing. One of the cities that is also experiencing development is Malang City, one of which is Ki Ageng Gribig road which is the access to Malang-Pandaan toll road. This study aims to determine the degree of saturation of Ki Ageng Gribig road section which is around Pandaan-Malang toll gate. This study used a quantitative method and was guided by the 1997 Indonesian Road Capacity Manual. The research was conducted on two sections of the road, before and after entering the toll road. Based on the data obtained from the research survey, the road capacity results were 1473.45 pcu/hour, with a Q value of 2476.1 pcu/hour on road section 1 and a Q of 3230.9 pcu/hour on road section 2. Then, the degree of saturation value obtained at peak hours on the road section 1 is 1.68 and section 2 is 2.19. Both sections of the road have an F value which indicates that this road segment is in a saturated condition. So that attention is needed from the community, especially road users, so that they can pay attention to land use on urban roads so as not to disturb the flow of traffic on Ki Ageng Gribig road.